The tourist movement in Ireland - Wilson, D. J. (Statistical and Social Inquiry Society of Ireland, 1906)
My paper should, I am aware, be devoted to a statistical and social review. I have discovered, however, that the subject is eminently one which does not lend itself to statistics, and I propose instead to treat it from a historical and an economic point of view?in the first place, endeavouring to justify the title of paper by showing that there is a Tourist Movement in Ireland, and next (assuming that I have succeeded in establishing this fact), dealing with its economic value to the country. In using the term historical I have no intention of diving into remote antiquity. Ireland has apparently always been a very attractive country, and has had a very varied list of visitors; but while some of them were extremely peripatetic, the "Tourist," in the modern sense of the word, is the evolution of comparatively recent times. I do not, therefore, propose to deal with the journeyings of Strongbow or the tours of Oliver Cromwell.
Read Friday, 19th April, 1901
Keywords: Tourist industry, Ireland; Tourist infrastructure, Ireland; 314.15